Analgesic Activity of Taxus Baccata Linn. Bark Extract - SATYAJIT DUTTA; ANURAG YADAV; G. MARIAPPAN (International Journal of Pharma and Bio Sciences, 2010)
In the traditional medicine, Taxus baccata Linn. has been used as analgesic, anticonvulsant, and anti-inflammatory remedy. In the present study, bark of plant was extracted with 95% ethanol and ether at room temperature and evaluate for their analgesic activity in mice using the tail-flick and acetic acid-induced writhing method. Ether extract exhibits potent analgesic activity in tail-flick test at 200mg/kg two hours after administration in compare with ethanolic extract, whereas ethanolic extract exhibits significant analgesic activity in acetic acid-induced writhing test at 200mg/kg. The extracted compounds exhibited analgesic activity against chemically and thermal noxious stimuli on both early and late phases of pain by the extracts (100 and 200 mg/kg doses). The observed pharmacological activities provide the scientific basis for the folkloric use of the plant in treating acute pain.